PENGEMBANGAN LKPD KONTEKSTUAL PADA MATERI SUHU, KALOR DAN PERPINDAHAN KALOR DI KELAS X SMA - Andriani, Andriani; Maison, Maison; Dani, Rahma (EduFisika: Jurnal Pendidikan Fisika, 2019)
This research aims to develop contextual LKPD in temperature materials, heat and displacement of X-grade SMA and to know the perception of learners. This research is a research and development that uses 4-D development model (Difine, Design, Develop, and Disseminate). The subject of trials in this study was a student of X-grade SMA Negeri 1 Jujuhan Bungo. Research instruments in the form of expert validation sheets and student perception polls. Data is analyzed descriptively. The resulting product is a contextual LKPD on temperature material, heat and heat transfer. Activities on the LKPD in accordance with the steps of contextual learning (constructivism, Inquisition, questioning, learning society, modeling, reflection and assessment). The validation results of expert material and media experts against LKPD stated to be worthy of use. The results of the learner's perception gained an average score of 4.27 (very good).